A survey on characterizing the empirical analysis, proposed approaches, and research trends for architectural decay - Baabad, Ahmed; Zulzalil, Hazura; Hassan, Saadah; Baharom, Salmi (IGI Global, 2022)
This decay does not happen overnight, but rather it's cumulative impacts over time. Even though the prior works covered various aspects concerning maintaining architecture from erosion, however, the common factor in the existing studies does not provide full detail about the empirical analysis, perceptions of the proposed approaches, and trendy track of the architectural decay research. There are existing review studies on analysis techniques and approaches of various architectural decay, but to the best of our knowledge, insufficient focus was considered on precisely the description of the empirical analysis, techniques, approaches, and trends for studies that have been evaluated concerning architectural decay. This study provides a comprehensive survey and detailed investigation on the empirical analysis regarding research design and its method, existing approaches analysis to identify used strategies, and trendy research to clarify trendy track for researchers and what evolves from a meaningful essential idea concerns the researchers within the architectural degradation field.